2022
DOI: 10.1002/adsu.202200074
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Molecule Modification toward Efficient Carbon‐Based All‐Inorganic CsPbIBr2 Perovskite Solar Cells

Abstract: Favorable stability is a big challenge for the commercialization of perovskite solar cells, and all‐inorganic perovskite semiconductors have attracted much attention due to their excellent performance in this field. In reality, the poor stability is mainly due to the high‐density defects in the perovskite films, which provide a channel for charge nonradiative recombination and ion migration. In this work, a multifunctional aminoguanidine hemisulfate (AG HSUL) is introduced into the CsPbIBr2 perovskite layer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Figure a,b shows the device structure and energy band diagram of the components of the PSCs respectively that we adopted in our study. The valence band maximum (VBM) of TEA 2 PbI 4 perovskite was estimated by UPS. As illustrated in Figure S8, the VBM is 5.48 eV and the conduction band minimum is 3.14 eV that we calculated from VBM and the optical bandgap (2.34 eV). The energy level diagram suggests that energy levels of the 2D perovskite match well with the pristine MAFA (3D) perovskite for facilitation of charge separation.…”
Section: Resultsmentioning
confidence: 98%
“…Figure a,b shows the device structure and energy band diagram of the components of the PSCs respectively that we adopted in our study. The valence band maximum (VBM) of TEA 2 PbI 4 perovskite was estimated by UPS. As illustrated in Figure S8, the VBM is 5.48 eV and the conduction band minimum is 3.14 eV that we calculated from VBM and the optical bandgap (2.34 eV). The energy level diagram suggests that energy levels of the 2D perovskite match well with the pristine MAFA (3D) perovskite for facilitation of charge separation.…”
Section: Resultsmentioning
confidence: 98%
“…3D profile of the BDA group in Figure 2c showed that BDA is mainly anchored on the perovskite surface. [36][37][38][39] The possible reason for this can be attributed to the fact that BDAI 2 assembles on perovskite grains, limiting the inclination of grains during the growth process, and finally forming a (100) oriented dominant film (Figure S6, Supporting Information). With the grain growth, BDAI 2 is finally discharged to the surface of perovskite films.…”
Section: Resultsmentioning
confidence: 99%
“…Various types of organic functional additives, such as organic molecules, [121,253,254] organic salts, [255,256] ammonium salts, [215,257] amino acids, [216,217,258] ionic liquids, [72,259] nanomaterials, [260] quantum dots (QDs), [261] and polymers, [23,[262][263][264][265][266][267] have been applied in CsBX 3 and their derivatives. For example, Wang et al incorporated piperazine-1,4-diium iodide (PZDI 2 ) into CsPbI 3 and confirmed the formation of RP perovskite (Figure 11e).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%